Isolation and Characterization of Broadly Neutralizing Human Monoclonal Antibodies to the E1 Glycoprotein of Hepatitis C Virus - Meunier, Jean-Christophe (American Society for Microbiology (ASM), 2008)
The relative importance of humoral and cellular immunity in the prevention or clearance of hepatitis C virus (HCV) infection is poorly understood. However, there is considerable evidence that neutralizing antibodies are involved in disease control. Here we describe the detailed analysis of human monoclonal antibodies (MAbs) directed against HCV glycoprotein E1, which may have the potential to control HCV infection. We have identified two MAbs that can strongly neutralize HCV-pseudotyped particles (HCVpp) bearing the envelope glycoproteins of genotypes 1a, 1b, 4a, 5a, and 6a and less strongly neutralize HCVpp bearing the envelope glycoproteins of genotype 2a. Genotype 3a was not neutralized. The epitopes for both MAbs were mapped to the region encompassing amino acids 313 to 327. In addition, robust neutralization was also observed against cell culture-adapted viruses of genotypes 1a and 2a. Results from this study suggest that these MAbs may have the potential to prevent HCV infection.